P2‐type NaxTmO2 oxides as cathodes for non‐aqueous sodium‐ion batteries—Structural evolution and commercial prospects. (15th August 2022) - Pahari, Debanjana; Kumar, Ananya; Das, Dhrubajyoti; Puravankara, Sreeraj
Summary: First‐generation sodium‐ion batteries (SIBs) are commercially launched by Faradion Ltd., UK, and HiNa Battery Technology Company Ltd., China, utilizing the transition metal oxide‐based cathodes. Currently, the commercial Faradion cells deliver ~1000 cycles at an energy density of ~140 to 150 Wh kg −1, whereas HiNa SIB cells deliver ~120 Wh kg −1 . P2‐type, O3‐type, and composite P‐O and P‐P type transition metal oxide cathodes have generated much interest in the last few years. P2‐type layered oxides are critical as cathodes in achieving higher energy and power density in SIB technology, along with better C‐rate capabilities. Compared to their O3‐type counterparts, P2‐type layered transition metal oxides encounter lower activation energy barriers, enabling improved rate kinetics. However, P2‐type cathodes often face poor cycle stability due to undesirable phase changes during charge‐discharge cycles and structural instability to air and moisture. This review evaluates all the P2‐type layered oxide compounds as SIB cathodes, highlighting the strategies followed to meet the challenges and offers aspects of their successful commercialization. Abstract : Insights into the prospects of P2‐type transition metal oxides as commercial cathodes for SIBs depend on sodium stoichiometry, high‐voltage phase transitions, anionic O2 redox at high potentials, and transition‐metal ion substitution to improve the specific capacity, cycle life, and rate capabilities of SIBs. The review comprehensively follows the structural evolution of P2‐type oxides from single‐metal oxide to quadra‐metal oxides in improving their cathode performance in non‐aqueous sodium‐ion batteries (SIB).